Kaposi’s Visceral Sarcoma in liver transplant recipient – a case report - Boin, Ilka de Fatima Santana Ferreira; Leonardi, Marília Iracema; Leonardi, Luiz Sérgio; Sampaio, Ana Maria; Cunha, Andréa Mendonça Gusmão; Costa, Sandra Cecília Botelho; Almeida, Jazon Romilson de Souza; Stucchi, Raquel Bello; Escanhoela, Cecília Amélia Fazzio (Brazilian Journal of Transplantation, 2006)
Since 1969, when the Kaposi’s sarcoma case was first described in a patient submitted to renal transplantation, there was an increase of such cases in other solid-organ transplant recipients. In our unit, the prevalence of the Kaposi’s sarcoma in renal transplantations was 3 out of 1000. The aim of this study was to report one Kaposi’s sarcoma case which appeared in a liver transplantation recipient. A man underwent orthotopic liver transplantation due to hepatitis C virus cirrhosis in February, 2002. Postsurgery status was very good, and the patient was discharged 20 days after OLT. The immunosuppressant protocol consisted to tacrolimus 0.1mg/kg/day and prednisone tapering from 100mg to 20mg. After two months, he showed weakness, polyphagia, polydipsia and polyuria, being diagnosed diabetes after the use of immunosuppressant drugs. The patient presented an improvement; however, afterwards the corticoids were withdrawn, and after the 5th month, he showed weight loss, fever, adynamia and diarrhea. Colonoscopy was normal, viral serology to HIV was negative. Liver function tests were normal. He was re-admitted in the hospital with epigastralgia, and the upper digestive endoscopy showed lesions compatible with KS in the stomach. Despite a reduction in the immunosuppressant drugs, the patient’s clinical conditions deteriorated and he died. Despite the early diagnosis, the visceral involvement was very aggressive. Serological and molecular HHV-8 detection (N-PCR -ORF 26) was prior to the diagnosis of visceral sarcoma, but this was achieved only four years late.